DEVELOPMENT OF THREE-DIMENSIONAL VISUAL LEARNING MEDIA "BUKU SUSUN MESIS" TO IMPROVE STUDENT LEARNING OUTCOMES ON ANIMAL LIFE CYCLE MATERIAL CLASS IV SUMBERJO 2 ELEMENTARY SCHOOL - Isabela Arinda Putri; Muhamad Basori; Wahid Ibnu Zaman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was carried out with the aim of finding out how to develop three-dimensional visual learning media for buku susun mesis on class IV animal life cycle material that is valid, practical and effective. This research is Research and Development (R&D). The development model used is the ADDIE model. The stages in the ADDIE model are 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Data was collected using observation, tests, questionnaires and documentation techniques. In analyzing the data, data was obtained from the results of expert validity tests, teacher and student practicality tests, and effectiveness tests obtained from student posttest results. The results obtained from this research were that the learning media developed received a validity percentage of 91.1% from material experts and 88.3% from media experts, resulting in an average of 89.7% with a very valid category. Meanwhile, the practicality test received 92.3% of teacher responses and 92.8% of student responses, resulting in an average of 92.5% in the very practical category. In the effectiveness test, the average student learning outcome was 85.6 with a classical learning completeness percentage of 87.5%, while in extensive trials the average student learning outcome was 92.3 with a classical learning completeness percentage of 90.9. %. From the two field trial results, an average percentage of 90.5 was obtained with an average percentage of classical learning completion of 90% in the very effective category. So it was concluded that the three-dimensional visual learning media "Buku Susun Mesis" can be used in learning.